2016
DOI: 10.1007/s00259-016-3517-z
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical in vivo and in vitro comparison of the translocator protein PET ligands [18F]PBR102 and [18F]PBR111

Abstract: [F]PBR102 and [F]PBR111 have distinct metabolic profiles in rat and non-human primates. Radiometabolites contributed to non-specific binding and confounded in vivo brain analysis of [F]PBR102 in rodents; the impact in primates was less pronounced. Both [F]PBR102 and [F]PBR111 are suitable for PET imaging of TSPO in vivo. In vitro metabolite studies can be used to predict in vivo radioligand metabolism and can assist in the design and development of better radioligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…V ND values we obtain with HYDECA average 27% of total binding in ventral striatum for [ 11 C]DASB, and 22% of the total binding in hippocampus for [ 11 C]CUMI-101, which is generally in line with reports for other PET tracers [31, 32]. …”
Section: Resultssupporting
confidence: 89%
“…V ND values we obtain with HYDECA average 27% of total binding in ventral striatum for [ 11 C]DASB, and 22% of the total binding in hippocampus for [ 11 C]CUMI-101, which is generally in line with reports for other PET tracers [31, 32]. …”
Section: Resultssupporting
confidence: 89%
“…The polar radiometabolite has been identified previously as 18 Ffluoropropionic acid (21). According to other studies, none of the radiometabolites entered the brain within 60 min after injection (21,22). Parent and metabolite profiles did not vary across the clinical groups.…”
Section: Discussionmentioning
confidence: 71%
“…Metabolite analysis revealed that 18 F-PBR111 rapidly decreased over time with formation of both polar and semiapolar radiometabolites in the arterial plasma. The polar radiometabolite has been identified previously as 18 Ffluoropropionic acid (21). According to other studies, none of the radiometabolites entered the brain within 60 min after injection (21,22).…”
Section: Discussionmentioning
confidence: 91%
“…In one such study, incubation of PBR102 and PBR111 with rat microsomes showed dealkylation and hydroxylation to be the predominant pathways, with lesser metabolism by human microsomes. 130 We summarize the metabolism of 13 tracers that have been employed in quantitative molecular imaging studies of TSPO in healthy human brain ( Table 1). There is substantial metabolism of most of these tracers during a dynamic PET/SPECT examination, such that proper quantitation of brain uptake entails chromatographic analysis of extracts from plasma derived from serial arterial blood sampling.…”
Section: Metabolism and Plasma Protein Bindingmentioning
confidence: 99%